Wholesale Bank Funding, Capital Requirements and Credit Rationing - Agur, Itai (IMF Working Papers; Working Paper ;, 2013)
This paper analyzes how different types of bank funding affect the extent to which banks ration credit to borrowers, and the impact that capital requirements have on that rationing. Using an extension of the standard Stiglitz-Weiss model of credit rationing, unsecured wholesale finance is shown to amplify the credit market impact of capital requirements as compared to funding by retail depositors. Unsecured finance surged in the pre-crisis years, but is increasingly replaced by secured funding. The collateralization of wholesale funding is found to expand the extent of credit rationing.